The Role of the Banking Industry in Enhancing Public Financial Inclusion - Maria G.S. Soetopo (Greenation International Journal of Law and Social Sciences, 2026)
The banking industry is a significant part of the financial services sector and continues to develop dynamically. However, this progress has not fully addressed society’s demand for diverse credit needs. Although the government has undertaken efforts to expand credit access and foster business growth through financial inclusion policies, challenges remain. This study examines how financial inclusion policies and credit distribution enhance the role of the banking industry in national economic development. This research employs a normative juridical method supported by economic analysis. The findings indicate the need to adjust the legal foundations of financial inclusion policies to align with societal developments and government economic strategies. The ultimate objective is to ensure legal certainty so that policy implementation can effectively realize the values of justice and utility.